Cultural Values in Idiomatic Expression of Jambi Malay Language Bungo Malay Dialect: Antropholinguistics Perspective - Dodi Oktariza; Dedi Efendi (Jurnal Ilmiah Langue and Parole, 2023)
This research is aimed to describe cultural values that found in the idiomatic expressions of Jambi Malay Language Bungo Malay dialect Then, the research is conducted through several steps, namely, collecting data, analyzing, and presenting the result of data analysis. The methods chosen in collecting data were observational and conversational method, by applying some techniques such as non participant observational technique, note taking technique, elicitation, and recording technique. Then, in analyzing technique, the writer used descriptive qualitative approach by using contextual analysis method in order to explain the cultural values from the expressions. Moreover, the writer used informal method for presenting the result of analysis. The result of research shows that the expressions of idiomatic from the Jambi Malay Language Bungo Malay dialect contain cultural values that have been developed in the society, especially for Jambi Malay speakers that categorized into good and bad values. Besides, the idiomatic expressions that used by Jambi Malay Language Bungo Malay dialect also contains ethics, moral, and politeness